A Proposed Algorithm for Retinex Computation in Image Enhancement Applications - Mohammed Saleh, Saad; Jasim Farhan, Malik; Hadi Wali, Musa (Journal of Engineering and Sustainable Development, 2007)
The Retinex is an image enhancement algorithm that improves the brightness, contrast and sharpness of an image. The core of Retinex computation is clearly specified in recent Matlab implementations. The recent Retinex algorithms use several free parameters to control the enhancement degree. In this paper we introduce a proposed algorithm for image enhancement using Retinex algorithm. The proposed algorithm based on the previous algorithms for Retinex computation, the major difference here is that the main control parameter for enhancement degree (enhancement factor) is computed automatically during processing according to a proposed relation introduced in this paper.The proposed relation depends on the illumination degree of the areas (blocks) of the scene under processing this is useful for very bad illumination scenes or images. This research also shows that the proposed algorithm is useful for the images with medium illumination.